Perananan Pelaksanaan Administrasi Kurikulum Pendidikan - Khairan Sari; Elsa Dwi Putri; Atika Ainur Rahman; Yessi Rifmasari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to study the concept of curriculum administration process. Curriculum is a set of plans and regulations regarding the content and learning materials and methods used as guidelines in the implementation of the teaching and learning process. The curriculum administration process consists of planning, implementation, monitoring and evaluation. The curriculum is a planning document that contains the objectives to be achieved, the content of the material and learning experiences that students must do, strategies and methods that can be developed, evaluations designed to collect information about the achievement of objectives, and the implementation of documents designed in real form. Thus, the curriculum plays an important role in the success of student education. One aspect that can increase the success of the curriculum is the administration of the implementation of the curriculum at the relevant educational institution, in other words, the implementation of the curriculum is institutional in nature. This study focuses on the literature study method by collecting literature (related materials) sourced from books, journals, and other sources related to the science of Administration. The term curriculum administration emphasizes efforts to direct the curriculum so that the curriculum can be implemented appropriately in various educational activities